The Effect Of Task-Based Instruction Method In Enhancing The Speaking Skills Of Eleventh Grade Students At MA Hubbulwathan Duri - Fido Faroza (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
The aims of the study were to examine the effect of Task-Based Instruction (TBI) on enhancing the speaking skills of eleventh-grade students at MA Hubbulwathan Duri. Using a quasi-experimental design with a quantitative approach, it compares students' speaking abilities before and after TBI implementation and examines differences between the experimental group (TBI) and the control group (traditional instruction). The research questions included: (1) How are students' speaking skills before using TBI? (2) How are students' speaking skills after using TBI? (3) Is there a significant difference in students' speaking skills after using TBI? Data analysis through paired t-tests showed that the experimental group demonstrated significant improvement in speaking skills, particularly in pronunciation, grammar, vocabulary, and fluency, after receiving TBI. Meanwhile, the control group, which received traditional instruction, showed minimal progress. The findings reveal a significant difference in speaking performance between the two groups, emphasizing TBI's effectiveness in enhancing speaking skills. This study highlights the potential of Task-Based Instruction as an effective teaching method for improving students' speaking Skills.